1999
DOI: 10.1177/0042085999343002
|View full text |Cite
|
Sign up to set email alerts
|

Redefining Education Regimes and Reform

Abstract: Governors across the country are playing a more important role in steering education policy than in the past. In our nine-state study of the politics of education from 1995 to 1997, the authors observed governors putting forward major reforms from vouchers to state standards and forming important coalitions with the business community and religious groups. Professional organizations, which have monopolized decision making in education for years, were forced to adjust to these new participants. Charter schools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Many studies find that as the chief executive, voters “look to governors to lead their states, credit them with any successes and hold them accountable for most failures” (Kousser & Phillips, , p. 1). Research has shown that governors are held accountable for general goals, such as economic development and economic performance (Atkeson & Partin, ; Cohen & King, ), as well as major policy innovations such as welfare reform (Haskins, ; Katz, ) and education reform (Gittell & McKenna, ; Perna & Finney, ). We expect this to be just as true for the decision to expand Medicaid, which represents one of the most salient policy decisions made at the state level in recent years.…”
Section: Theorizing the Link Between Medicaid Expansion And Gubernatomentioning
confidence: 99%
“…Many studies find that as the chief executive, voters “look to governors to lead their states, credit them with any successes and hold them accountable for most failures” (Kousser & Phillips, , p. 1). Research has shown that governors are held accountable for general goals, such as economic development and economic performance (Atkeson & Partin, ; Cohen & King, ), as well as major policy innovations such as welfare reform (Haskins, ; Katz, ) and education reform (Gittell & McKenna, ; Perna & Finney, ). We expect this to be just as true for the decision to expand Medicaid, which represents one of the most salient policy decisions made at the state level in recent years.…”
Section: Theorizing the Link Between Medicaid Expansion And Gubernatomentioning
confidence: 99%
“…Culture involves values and beliefs that persist over very long periods and are more enduring than the political mood or regime (Gittell and McKenna 1999;Kingdon 1984;Manzer 2003). Both political cultures and regimes support or restrict policy choices that may be invented or adopted by policy entrepreneurs.…”
Section: Studies Of State Education Policy Makingmentioning
confidence: 99%
“…Scholars contend that governors and state legislatures steer but fail to ultimately decide urban education policy (Gittell & McKenna, 1999). They argue that state governments lack the capacity to implement education policy and they claim that local school districts determine education policy (Turnbull, 1984;Firestone, 1984).…”
Section: Urban Education Regimes and State Governmentmentioning
confidence: 99%
“…It argues that local players place the final imprint upon, and ultimately determine, urban education policy (Gittell & McKenna, 1999;Stone, 1998b). For example, Hochschild and Danielson (1998) and McDermott (1999) found that local forces successfully resisted state government's efforts to desegregate school districts in Yonkers, New York, and New Haven, Connecticut.…”
mentioning
confidence: 99%